Applying IS-Enabled Telework during COVID-19 Lockdown Periods and Beyond: Insights from Employees in a Greek Banking Institution - Georgios Stamos; Dimosthenis Kotsopoulos (Administrative Sciences, 2024)
The recent circumstances of the COVID-19 crisis have brought significant changes to employees’ personal, as well as organizational, lives. For office workers worldwide, this has come as a result of the abrupt and wide adoption of telework, as organizations rushed to accelerate their digital transformation. This research focuses on analyzing the reception and effect of teleworking, as an imposed measure during the onset of the COVID-19 pandemic, on employees in Greek banking organizations. First, the circumstances and utilization of telework by a banking institution in Greece before and during the COVID-19 crisis are compared by utilizing autoethnographic evidence. Then, we conducted qualitative research with employees of the organization, who were asked to work remotely at 100% capacity, focusing on the way teleworking was performed utilizing information systems (IS), and the effect it had on them. Detailed information and results from interviews are presented and compared to autoethnographic evidence to reach our conclusions. We find that the vast majority of employees are in general positive about having telework as an option, while the time saved by not commuting to their offices is reported as the most positive element of telework. Most employees also reported having worked longer hours and more efficiently while teleworking, while a common concern—in a scenario where telework may become permanent in some form—is if the organization would cover their teleworking expenses. Theoretical and practical implications are explored and presented accordingly.